2022
DOI: 10.20344/amp.16898
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing or Feedback: Exploring the Impact of Two Post-Scenario Discussion Methods in the Acquisition and Retention of Non-Technical Skills

Abstract: Introduction: There is a paucity of quantitative studies objectively comparing debriefing and feedback as methods for post-scenario discussion and its impact on healthcare teams’ acquisition and retention of non-technical skills. The main purpose of this study is to provide some insight on this research question, using a sample of medical students. A secondary objective explores students’ opinion and preference on the post-scenario discussion.Material and Methods: Forty-five medical students were distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…23 Sá-Couto et al, in a recent study, showed that debriefing after a simulation scenario improves the acquisition and retention of non-technical skills, in undergraduate students. 13 Our study assessed whether the medical students' non-technical skills and team performance in simulated trauma scenarios could be developed, trained and retained after some time. Baker et al ran a similar study in undergraduate students, from different healthcare programs (physicians, nurses, radiology department and respiratory care), testing their ability to acquire teamwork skills using team-based learning with Team STEPPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Sá-Couto et al, in a recent study, showed that debriefing after a simulation scenario improves the acquisition and retention of non-technical skills, in undergraduate students. 13 Our study assessed whether the medical students' non-technical skills and team performance in simulated trauma scenarios could be developed, trained and retained after some time. Baker et al ran a similar study in undergraduate students, from different healthcare programs (physicians, nurses, radiology department and respiratory care), testing their ability to acquire teamwork skills using team-based learning with Team STEPPS.…”
Section: Discussionmentioning
confidence: 99%
“…After each simulation, there was a structured debriefing, facilitated by the most experienced instructor. 13 All team scenarios were originally created by the last author based on the European Trauma Course model.…”
Section: Methodsmentioning
confidence: 99%
“…O feedback é baseado num diálogo estruturado de informação unidirecional entre o instrutor e o formando onde se apontam os aspetos positivos e a atitudes a modificar. 1 Estão definidos quatro pontos de estruturação do processo, originando assim diferentes tipos de debriefing, nomeadamente: tempo, dinamizador, fases do processo e técnicas a ser utilizadas. 5 Relativamente ao tempo, o debriefing pode ser realizado no meio do evento ou no final.…”
Section: Caro Editorunclassified